Legal Basis for the Application of the Law of Will in Contractual Obligations - Ronza Abdul Reda Naeem (Periodica Journal, 2023)
Despite the common circulation of the law of will, it sparked a jurisprudential debate about the legal basis on which the law of will was based, so there are different theories of jurisprudence as a basis for the application of the law of will in contractual obligations, including this personal theory and objective theory.
Keywords: personal; objective; jurisprudence; debate